Effectiveness of germicidal ultraviolet light to inactivate coronaviruses on personal protective equipment to reduce nosocomial transmission. (21st July 2022) - Camargo, Carolina; Lupien, Andréanne; McIntosh, Fiona; Menzies, Dick; Behr, Marcel A.; Sagan, Selena M.
Abstract: Objective: To circumvent the need for rationing personal protective equipment (PPE), we explored whether germicidal ultraviolet light (GUV) could be used to inactivate human coronaviruses on PPE, enabling safe reuse. Design: We performed a laboratory study to assess the ability of 2 commercially available portable GUV devices to inactivate 2 common cold coronaviruses (HCoV-229E and HCoV-OC43) and severe acute respiratory syndrome coronavirus virus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), on the surface of whole N95 respirators and coupons cut from those respirators. We experimentally contaminated N95 respirators with coronavirus cultures and then assessed viral inactivation after GUV exposure by plaque assay, the median tissue culture infectious dose (TCID50 ) assay, and quantitative reverse-transcriptase polymerase chain reaction (RT-PCR). Results: We found that GUV could efficiently inactivate coronaviruses on the surface of N95 masks, with an average reduction in viral titers of 5-log for HCoV-229E, 3-log for HCoV-OC43, and 5-log for SARS-CoV-2. In addition, the GUV susceptibility of HCoV-229E was similar on coupons and whole N95 respirators. Conclusions: We demonstrate that diverse human coronaviruses, including SARS-CoV-2, are susceptible to GUV inactivation, and 2 scalable portable GUV devices were effective in inactivating coronaviruses on N95 respirators. Thus, GUV treatment with commercially scalable devices may be an effective method to decontaminate PPE, allowing their safe reuse.